Climatic Factors as Determinants of International Migration - Michel Beine; Christopher Parsons (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
We examine environmental change as a potential determinant of international migration. We distinguish between unexpected short-run factors, captured by natural disasters, as well as long-run climate change and climate variability captured by deviations and volatilities of temperatures and rainfall from and around their long-run averages. Starting from a simple neo-classical model we use a panel dataset of bilateral migration flows for the period 1960-2000 that allows us to control for numerous time-varying and time invariant factors. We find no direct impact of climatic change on international migration across our entire sample. These results are robust when conditioning on characteristics of origin countries as well as when further considering migrants returning home and the potential endogeneity of our network variable. In contrast, there is evidence of indirect effects of environmental factors going through wages. We further find strong evidence that natural disasters beget greater flows of migrants to urban environs.
Keywords: F22; O15; 330